1996
DOI: 10.2355/isijinternational.36.suppl_s30
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Calcium in Calcium-Calcium Halide Fluxes.

Abstract: The activities of calcium in the Ca0~*td -Ca-CaX2fluxes (X: Cl. Br. l) The experimental results for the Ca0~*td.-Ca-CaC12, CaOsatd.~Ca-CaBr2and CaO**td -Ca-Cal2 systems are summarized in Tables 1, 2, and 3, respectively. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…For the determination of equilibrium constants, the activities of the solved elements are used analytically determined apparent values and are not corrected by interaction parameters, because the solved contents are quite small and its influences are also expected to be quite small. Although the activity of calcium in the molten slag (CaOAl 2 O 3 ZrO 2 ) must be thermodynamically determined, because the metallic calcium seems to be hardly solved in oxygen-based salt, 39,40) the activity of calcium, a Ca , in the molten salt is defined to be "1". Then, the equilibrium constant of the reaction is conveniently determined to be ¹3.4 (= log K), as the intercept of the fitting line for the oxygen concentration by the least squares method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the determination of equilibrium constants, the activities of the solved elements are used analytically determined apparent values and are not corrected by interaction parameters, because the solved contents are quite small and its influences are also expected to be quite small. Although the activity of calcium in the molten slag (CaOAl 2 O 3 ZrO 2 ) must be thermodynamically determined, because the metallic calcium seems to be hardly solved in oxygen-based salt, 39,40) the activity of calcium, a Ca , in the molten salt is defined to be "1". Then, the equilibrium constant of the reaction is conveniently determined to be ¹3.4 (= log K), as the intercept of the fitting line for the oxygen concentration by the least squares method.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of calcium, a Ca , is difficult to be determined from information in the literature. However, the activity, a Ca , of the metallic calcium for CaOCaCl 2 melts was investigated by some researchers 39,40) and found to be "1" for a content of calcium of 1 to 4 mol% in the melts. Therefore, it is reasonable that the calcium activity, a Ca , of most cases in these studies is expected to be "1".…”
Section: Discussionmentioning
confidence: 99%
“…It can be predicted that dephosphorization of ferrosilicon and silicomanganese by calcium treatment is a promising process, although its extent is strongly dependent on the calcium activity, which has been measured recently for molten halide systems. [14,15] …”
Section: Rtmentioning
confidence: 98%
“…On the basis of the above thermodynamic discussion, the sulphur distribution ratio, LS, is finally calculated to be 4.7×10 6 . Considering that the sulphur distribution ratios are around 10 3 at largest for conventional refining operation, it can be concluded that Ca-CaF2 flux has extraordinarily high desulphurisation ability due to intrinsic strong reducing ability of calcium in spite of relatively high activity coefficient of CaS.…”
Section: Desulphurisation Ability Of Ca-caf2 Fluxmentioning
confidence: 99%
“…In this regard, several studies have been made on calcium-calcium halide flux with intention of the dilution of calcium, aiming at dephosphorisation [1][2][3] and denitridation. 4) Furthermore, some researchers have reported successful removal of various tramp elements 5,6) such as tin, antimony, arsenic and bismuth by Ca-CaF2 flux. In an ESR(electro-slag remelting) operation, Nakamura 7) has demonstrated very effective simultaneous removal of phosphorus and tramp elements in stainless steel.…”
Section: Introductionmentioning
confidence: 99%